PROSPECTS FOR THE DEVELOPMENT OF MODERN SCIENCE: EDUCOLOGICAL ASPECTS - Olga Melnychenko (Borys Grinchenko Kyiv Metropolitan University, 2023)
The article is devoted to the analysis of futurological research as a scientific method of forecasting the future development of society in general and the educational sphere in particular. The author provides a general description of futurology, reveals the specifics of future research and singles out the methods and technologies used by futurology. The fact is emphasized that unlike astrology or utopian concepts, futurology relies in its forecasts on a set of methods borrowed from other scientific fields. The article emphasizes the importance of analyzing past and present events, developing alternative options for the future development of society in general and education in particular. The author emphasizes the interdisciplinarity and transdisciplinarity of futurological research and draws a parallel between futurology and educology as scientific directions that aim to predict future social development, determine its trends and specifics. The author pays special attention to the characteristics of the complex of research methods of futurology, as borrowed from the natural sciences, in particular mathematics, physics, cybernetics, etc. The article highlights the trends and directions of education development, which will be the main guidelines for the quality of education in the future. Futurology is a branch of social knowledge that deals with the analysis and development of concepts of the future by extrapolation of existing technological, economic or social trends, as well as substantiating the forecast of the development of future trends. Extrapolation is just one of the methods used by futurists when studying the future. When developing futurology, scientists aimed to create a new science, a kind of «philosophy of the future», which would focus on scientific and theoretical exploration and oppose utopian concepts. Today, futurology is considered as a science that is free from any ideological and socio-utopian doctrines, as a branch of social science, the task of which is to develop concepts of the future of humanity, prospects for the development of social processes. The main problems that modern futurology is interested in: 1) definition and evaluation of future development trends, in particular in the educational sphere. To do this, first, some current development trends are singled out and an attempt is made to characterize them in a certain way, to determine their possible influence on each other, and to describe their possible interaction under various scenarios; 2) identification of regularities among a variety of specific single determinants; 3) coverage of the analysis of the entire system (for example, the educational sphere), based on the identified trends and components of development; 4) forecasting the development of the system in the short-term and long-term perspective, including its development during the century under various possible circumstances; 5) using a combination of instincts and logic during research, and not just rational thinking.